Pengaruh ISO 9001: 2015, motivasi, dan kompetensi terhadap kinerja pustakawan di Perpustakaan Universitas Hasanuddin - Chusnul Chatimah Asmad; Abdul Rahman Rahim; Andi Jaman (Universitas Padjadjaran, 2019)
Motivation and competence can be variables that affect the level of librarian performance. ISO 9001: 2015 can also affect librarian performance as there is a quality management system clause that focuses on human resources in the organization. Therefore, the purpose of this research was to find out and analyze the influence of ISO 9001: 2015, motivation, and competence partially and simultaneously on the performance of librarians in the UNHAS Library. This study used quantitative survey research, with a total population of 42 people. The sample was the entire population. The results showed that motivation and competence partially had a significant effect on the performance of librarians. This is consistent with the opinions of several experts and relevant studies. Furthermore, ISO 9001: 2015 did not have a significant partial effect. These findings indicated that ISO in the UNHAS Library could not reach the realm of librarian performance improvement, one of which was due to the lack of librarian understanding of commitment and quality policy in ISO 9001: 2015. Based on the f test, it discovered that simultaneously, all independent variables had a significant effect on the dependent variable of 53,863. In conclusion, based on the regression test, it finds out ISO 9001: 2015 has no partial effect; however, it is simultaneous when integrated with motivation and competence variables, whereas motivation and competence variables can partially influence the performance of the UNHAS Library librarian.